(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Afrequently recurring theme in Williams’ plays relates to illusion-reality.Illusion and reality are the two poles on which his plays often turn. FrancisDonahue says, “ Behind Williams’ outer dramatic world of sex, violence,neuroticism, homosexuality and personal frustration, lie such basic themes asthe conflict between reality and illusion, the destruction of sensitive by theinsensitive and the human corrosion wrought by time” (Preface).